Logic-semantic and functional characteristics of somatisms in the lexical paradigm of the Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article is devoted to the research of lexical-semantic invariants of somatic objects, their functional characteristics; there have been analyzed the word definitions of substantive-somatisms such as body, head, leg etc., polysemy of their semantics, conditions and ways in which these units were used in early-printed texts as well as in “Hypathian Chronicle” . From the diachrony point of view the author analyzes the inner form of somatisms which produces numerous culturally meaningful connotations. Considerable attention is paid to various paradigms and oppositions which combine these most ancient by their origin words. Related to one and the same fragment of reality – anatomy of man and animals – they often, in the most unexpected relations and format, reflect the conceptual, substantive and functional similarity of the denoted phenomena. It was established that the substantive ‘body’ is dominant in frequency of use, and its semantic content is polysemantic. Examples which demonstrate the use of appellatives in early-printed texts being motivated by somatisms indicate that the latter seem to take over the function of the stimulus to establish various types of connections between the attribute and the defined word: potential, metaphorical, associative, differential, etc. In most of attributive phrases, adjectives do not introduce a new quality in the semantics of the defined noun-somatism, they mostly confirm the most characteristic organic feature of man.It is emphasized that the complex analysis of lexemes to denote anatomical parts of the body in the early-printed texts confirms not only their communicative relevance, but also the prospects in the study of the word ambiguity, metaphorical semantics, fixation of neologisms, motivated by somatisms. Many anatomical denominations used to denote the parts of the human body have acquired a symbolic meaning, which is explained by the nature of denotations, since their symbolic essence is particularly transparent: the word-somatism and the etalon which it symbolizes, interact and interpenetrate, gaining additional connotations.
Keywords: somatism; polysemy; connotative semantics; semantic invariant